The Value of E-Learning for the Prevention of Healthcare-Associated Infections - Labeau, Sonia O.; Rello, Jordi; Dimopoulos, George; Lipman, Jeffrey; Sarıkaya, Aklime; Öztürk, Candan; Vandijck, Dominique M.; Vogelaers, Dirk; Vandewoude, Koenraad; Blot, Stijn I. (Cambridge University Press, 2016)
BACKGROUND. Healthcare workers (HCWs) lack familiarity with evidence-based guidelines for the prevention of healthcare-associated infections (HAIs). There is good evidence that effective educational interventions help to facilitate guideline implementation, so we investigated whether e-learning could enhance HCW knowledge of HAI prevention guidelines. METHODS. We developed an electronic course (e-course) and tested its usability and content validity. An international sample of voluntary learners submitted to a pretest (TO) that determined their baseline knowledge of guidelines, and they subsequently studied the e-course. Immediately after studying the course, posttest 1 (T1) assessed the immediate learning effect. After 3 months, during which participants had no access to the course, a second posttest (T2) evaluated the residual learning effect. RESULTS. A total of 3,587 HCWs representing 79 nationalities enrolled: 2,590 HCWs (72%) completed TO; 1,410 HCWs (39%) completed T1; and 1,011 HCWs (28%) completed T2. The median study time was 193 minutes (interquartile range [IQR], 96-306 minutes). The median scores were 52% (IQR, 44%-62%) for TO, 80% (IQR, 68%-88%) for T1, and 74% (IQR, 64%-84%) for T2. The immediate learning effect (TO vs T1) was +24% (IQR, 12%-34%; P < .001), and a residual effect (TO vs T2) of +18% (IQR 8-28) remained (P < .001). A 200-minute study time was associated with a maximum immediate learning effect (28%). A study time >300 minutes yielded the greatest residual effect (24%). CONCLUSIONS. Moderate time invested in e-learning yielded significant immediate and residual learning effects. Decision makers could consider promoting e-learning as a supporting tool in HAI prevention.
WOS: 000382896800007
PubMed ID: 27174463